The study of the influence of service quality, service fairness and trust on customer loyalty in the Malaysian motor insurance industry - Hashim, Haslinda; Abdul Aziz, Yuhanis; Hamid, Abu Bakar Abdul; Kwong, Chee Kueng (Inderscience Publishers, 2023)
The objective of this study was to examine the influence of service quality and service fairness on customer loyalty in the Malaysian motor insurance industry. Further, it also aimed to examine how the above relationships mediated by trust. The quantitative research was conducted based on 399 completed survey questionnaires collected on convenience sampling basis within Klang Valley, Malaysia. The analysis of the study primarily based on partial least square-structural equation modelling (PLS-SEM) approach using the Smart PLS 3.0 software. The result indicated that both service quality, service fairness and trust had a significant positive influence on customer loyalty with trust appeared to be a significant mediation variable which partially mediates the relationship between the constructs understudied. This study observed that service fairness which mediated by the trust had a more substantial impact on the determination of customer loyalty for motor insurance relationship exchange as compared to service quality.